DESKRIPSI SISTEM INTEGRASI SAPI SAWIT (SISKA) DI KLASTER RIMBA MAKMUR KABUPATEN SANGGAU - Setiawan, Duta (Jurnal Sains dan Teknologi Industri Peternakan, 2025)
Sanggau is one of the palm oil-producing districts in West Kalimantan Province. This region has an oil palm plantation area of 327,417 Ha, or 26.18% of the area of Sanggau Regency. One of the oil palm plantations in Sanggau Regency was PTPN XIII, which is located in Semerangkai village. The integration of cattle grazing on oil palm plantations has been ongoing for years. This research aims to find out the description of SISKA in the Rimba Makmur Cluster, including smallholders' characteristics, and the Livestock rearing system. The type of research used was descriptive qualitative, with data collection carried out through interviews and questionnaires with cattle rearing who were integrating with oil palm. The data analysis used is descriptive qualitative. The research results show that the characteristics of breeders have an education level of 50% junior high school graduates and 40% farming experience raising cattle for 20 year. The cluster population of 275, there are 73 males and 202 females. The average body condition score (BCS) value is 3. The cattle-rearing system in oil palm plantations utilizes rotational grazing and is equipped with electric fencing. A cattle population of 275 heads only requires an oil palm area of 275 Ha out of a total grazing land of 596 Ha, so 321 AU can still increase the population..